Genome-wide analysis of EgEVE_1, a transcriptionally active endogenous viral element associated to small RNAs in Eucalyptus genomes - Marcon, Helena Sanches [UNESP]; Costa-Silva, Juliana; Lorenzetti, Alan Péricles Rodrigues; Marino, Celso Luis [UNESP]; Domingues, Douglas Silva [UNESP] (FapUNIFESP (SciELO), 2017)
Endogenous viral elements (EVEs) are the result of heritable horizontal gene transfer from viruses to hosts. In the last years, several EVE integration events were reported in plants by the exponential availability of sequenced genomes. Eucalyptus grandis is a forest tree species with a sequenced genome that is poorly studied in terms of evolution and mobile genetic elements composition. Here we report the characterization of E. grandis endogenous viral element 1 (EgEVE_1), a transcriptionally active EVE with a size of 5,664 bp. Phylogenetic analysis and genomic distribution demonstrated that EgEVE_1 is a newly described member of the Caulimoviridae family, distinct from the recently characterized plant Florendoviruses. Genomic distribution of EgEVE_1 and Florendovirus is also distinct. EgEVE_1 qPCR quantification in Eucalyptus urophylla suggests that this genome has moreEgEVE_1 copies than E. grandis. EgEVE_1 transcriptional activity was demonstrated by RT-qPCR in five Eucalyptus species and one intrageneric hybrid. We also identified that Eucalyptus EVEs can generate small RNAs (sRNAs),that might be involved in de novo DNA methylation and virus resistance. Our data suggest that EVE families in Eucalyptus have distinct properties, and we provide the first comparative analysis of EVEs in Eucalyptus genomes.
Keywords: Caulimovirus; Eucalyptus; Horizontal transfer; Insertion; Pararetrovirus